Subsidy-Related Deception Behavior in Energy-Saving Products Based on Game Theory - Zhao, Ni; Xia, Tongshui; Yu, Tao; Liu, Changyu (Frontiers in Energy Research, 2020)
The appropriate use of subsidies is the key to promote the development of energy-saving products (ESPs). However, subsidy-related deception behavior frequently occurs. Considering the relevant stakeholders, a game model including governments’ subsidy policies, manufacturers’ environmental quality measures, and customer environmental awareness (CEA) was constructed. We analyzed the crucial influencing factors of governments’ and manufacturers’ strategies. Quantitative analyses were performed to verify the modeling analyses and to demonstrate the influence of the game parameters. The results indicate that government regulation is necessary to keep manufacturers honest. Increases in penalties, the subsidy coefficient, environmental quality, and CEA all promoted manufacturer integrity. The results further reveal that the equilibrium probability of manufacturer’s integrity decreased with both the sales price of ESPs and the cost of government inspections. Moreover, as the cost coefficient of ESPs increased, the government enhanced the relevant regulations. Collectively, these results suggest strategies to reduce subsidy-related deception behavior and improve the effectiveness of government regulations.